Development of imperial universities as a sociocultural factor of establishing of higher pedagogical education in Ukraine (Pedagogy of Higher and Secondary Education, 2013)
Sombamaniya H. N. Development of imperial universities as a sociocultural factor of establishing of higher pedagogical education in Ukraine.The article is devoted to summarizing the features of imperаtorskiy universities as sources of origin of higher pedagogical education in Ukraine. Special attention is paid to the analysis of the organization of the theoretical and practical aspects of pedagogical teacher training of the graduates of classical university.
Keywords: classical university; organization of pedagogical teacher training